Hubungan Daya Ledak Otot Tungkai Dengan Kecepatan Lari 50 Meter Pada Atlet Usia Dini Binaan Dispora Aceh Jaya - Boihaqi, Boihaqi; Jalaluddin, Jalaluddin; Hidayat, Rahmat (Journal of Technology and Literacy in Education, 2024)
The title of this research is "The Relationship between Leg Muscle Explosive Power and 50 Meter Running Speed ​​in Early Age Athletes Assisted by the Aceh Jaya Youth and Sports Department. Based on the background of the problem above, the author wrote the main problem, namely: "Is there a relationship between the explosive power of the leg muscles and the speed of running 50 meters in young athletes assisted by the Aceh Jaya Sports and Sports Department? The aim of the research is to find out whether there is a relationship between leg muscle explosive power and 50 meter running speed in young athletes assisted by the Aceh Jaya Sports and Sports Department. After this research is carried out, it will reveal the relationship between leg muscle explosive power and 50 meter running speed in Early Age Athletes assisted by the Aceh Jaya Sports and Sports Department. Furthermore, the results of this research are expected to have the following benefits: (1) As a guide for sports teachers or coaches in developing running training methods, especially those related to leg muscle explosive power and 50 meter running performance in Early Age Athletes assisted by the Aceh Jaya Sports and Sports Department. (2) As reference material for further research. Based on the opinion above, this research is included in correlational descriptive research. The population in this study were all Early Age Athletes assisted by the Aceh Jaya Youth and Sports Department, totaling 15 students. By using a technique (total sampling), the researchers took 15 athletes as samples. Data collection in this research used test and measurement techniques. After the data has been obtained from field collection, it is processed using statistical formulas. Based on the results of research carried out by the author regarding the relationship between leg muscle explosive power and 50m running ability in young athletes assisted by Aceh Jaya Sports and Sports, the author will put forward several conclusions as follows: Based on the correlation analysis of leg muscle explosive power with 50m running ability, it can be concluded It was concluded that there was a relationship between the explosive power of leg muscles and the 50m running ability of young athletes assisted by the Aceh Jaya Sports and Sports Department of 50.52%.